Camisia (Camisia) horrida - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 258, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Camisia (Camisia) horrida (Hermann, 1804) Material – One specimen in Aluçdağı National Park, N 40° 49′ 7537′′, E 32° 58′ 2646′′, alt. = 1402 m, 17 July 2018, soil. Previous record in Turkey – Sivas (Toluk and Akın 2017). Global distribution – Holarctic. Ecology – Soil, moss, frequent on tree trunks and canopy.
Keywords: Arthropoda; Camisia; Arachnida; Crotoniidae; Animalia; Biodiversity; Sarcoptiformes; Camisia horrida; Taxonomy; 15. Life on land